NFTs And Branding: A Marketer's Guide to The Digital Art Craze - Shinta Rahmani; Edita Rachma Kamila; Cynthia Eka Violita (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research explores the integration of Non-Fungible Tokens (NFTs) into branding strategies within PT. BISI International, TBk, focusing on the agricultural sector. Utilizing a quantitative approach with a sample of 80 participants, the study investigates the direct and indirect effects of Social Media Engagement (SME) and Marketing Strategy Adoption on Consumer Perception and Market Understanding of NFTs and Branding. The findings reveal significant direct effects of Social Media Engagement and Marketing Strategy Adoption on Consumer Perception and Market Understanding of NFTs and Branding, highlighting the pivotal role of social media engagement and strategic adoption of NFTs in shaping consumer perception and market understanding. Moreover, the study identifies a significant indirect effect of Social Media Engagement on Market Understanding of NFTs and Branding through Consumer Perception, underscoring the mediating role of consumer perception in driving market understanding. However, the indirect effect of Marketing Strategy Adoption on Market Understanding of NFTs and Branding through Consumer Perception is found to be non-significant, suggesting a nuanced relationship between marketing strategy adoption, consumer perception, and market understanding. These insights provide valuable implications for marketers seeking to leverage NFTs to enhance brand positioning, consumer engagement, and market understanding within the agricultural sector.